A theorem on localized self-adjointness of Shrödinger operators with LLOC1-potentials - Hans L. Cycon (International Journal of Mathematics and Mathematical Sciences)
We prove a result which concludes the self-adjointness of a Schrödinger operator from the self-adjointness of the associated localized Schrödinger operators having LLOC1-Potentials.